Agrotourism Development Strategy in Wonogiri - suswadi; Diego Hermacho; Agung Prasetyo; Kusriani Prasetyowati (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
This study aims to analyze and identify internal and external environmental factors, describe marketing strategies, and describe the priority strategies used by Soko Langit Agrotourism. The data processing and analysis method uses the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation) matrix, the IE (Internal-External) matrix, the SWOT matrix (Strengths, Weaknesses, Opportunities, Threats), and QSPM (Quantitative Strategic Planning Matrix). The study results were obtained from five internal and five external factors, which resulted in eight alternative strategies in the marketing of Soko Langit Agrotourism. This study resulted in three strategic priorities related to visitor satisfaction, including a) improving the quality of facility maintenance; b) adding and maintaining rides in order to compete with competitors; and c) taking advantage of capital opportunities from the village government to reduce the number of loans from banks. Recommendations for strategies that can be implemented include: allocating capital opportunities from the village government for facility maintenance costs; adding rides with manageable maintenance levels; improving facilities that accommodate extreme weather changes; increasing the efficiency of financing from bank loans; and increasing the efficiency of facilities to accommodate extreme weather.